Stay Socially Distant and Wash Your Hands: Using the Health Belief Model to Determine Intent for COVID-19 Preventive Behaviors at the Beginning of the Pandemic. (August 2021) - Guidry, Jeanine P. D.; O'Donnell, Nicole H.; Austin, Lucinda L.; Coman, Ioana A.; Adams, Jay; Perrin, Paul B.
Background: The COVID-19 pandemic has quickly spread around the world, and since currently no treatments that are safe and effective for large groups of people nor a vaccine are available, the best way to prevent the illness is to avoid being exposed to the virus causing it. The purpose of this study was to examine the predictive effects of both demographic and psychosocial factors originating with the Health Belief Model on reported intent to adhere to COVID-19 preventive behaviors (e.g., social distancing, hand washing, and not attending large gatherings). Method: A Qualtrics survey of 500 U.S. adults was conducted to explore the relationships of demographics and psychosocial factors with the intent to adhere to COVID-19 preventive measures. Results: Gender was a predictor of taking preventive action, with women more likely to take action. Health Belief Model constructs predicted uptake of most COVID-19 preventive actions, but the constructs often appeared to work independent of the model. Race/ethnicity was an infrequent predictor, but when it did, minorities were less likely to report intent to adhere to COVID-19 preventive behaviors. Conclusion/Implications: While not a perfect model for this pandemic, the Health Belief Model and its constructs should continue to be considered for use by public health communicators focusing on preventive measure campaign design in both the COVID-19 pandemic era and beyond.